(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
In an array of symbolic animals the donkey has an outstanding relevance for what about its performative function. In many plots, the donkey plays an unexpected role, expressing itself with a terrible and frightening voice. His existential parable, traced by numerous stories of the Greek and Latin literature, as well as Hebrew-Christian tradition, responds well to the Schechnerian assumption of a behavior readable "as performance".